2014
DOI: 10.1155/2014/138016
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Chronic Lyme Disease to Family Medicine as a Complex Multidimensional Chronic Disease Construct: A Systematic Review

Abstract: Lyme disease has become a global public health problem and a prototype of an emerging infection. Both treatment-refractory infection and symptoms that are related to Borrelia burgdorferi infection remain subject to controversy. Because of the absence of solid evidence on prevalence, causes, diagnostic criteria, tools and treatment options, the role of autoimmunity to residual or persisting antigens, and the role of a toxin or other bacterial-associated products that are responsible for the symptoms and signs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 131 publications
0
14
0
Order By: Relevance
“…33 Therefore, as a recent review concluded: “There is a need for the development and establishment of new clinical diagnostic tools with increased accuracy, sensitivity, and specificity…”. 34 A validated symptom questionnaire would be valuable in the diagnosis of chronic Lyme disease/posttreatment Lyme disease syndrome (PTLDS) where seronegativity is a well-established phenomenon. 28 , 29 , 35 …”
Section: Background and Overviewmentioning
confidence: 99%
“…33 Therefore, as a recent review concluded: “There is a need for the development and establishment of new clinical diagnostic tools with increased accuracy, sensitivity, and specificity…”. 34 A validated symptom questionnaire would be valuable in the diagnosis of chronic Lyme disease/posttreatment Lyme disease syndrome (PTLDS) where seronegativity is a well-established phenomenon. 28 , 29 , 35 …”
Section: Background and Overviewmentioning
confidence: 99%
“…Multi‐systemic symptoms include fevers, fatigue, musculoskeletal, and nerve pain which may be migratory in nature , cardiovascular and neuropsychiatric symptoms with cognitive difficulties, and insomnia . The severity of clinical manifestations is often explained by HLA status and autoimmunity , differences in Borrelia genotypes , associated co‐infections , underlying medical problems increasing inflammation and immune responsiveness . Common variable immune deficiency (CVID) is the most common immunodeficiency syndrome , which is often associated with autoimmune phenomenon and when it is present in patients with Lyme disease and associated bacterial infections, might increase the severity of their illness.…”
Section: Introductionmentioning
confidence: 99%
“…Lyme borreliosis, also known as Lyme disease, is the most common tick-borne disease in North America and Europe [ 1 , 2 ]. The disease is initiated by an infection with a member of at least 19 species of bacteria in the Borrelia genus known as the Lyme borreliosis group or Borrelia burgdorferi sensu lato [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%